Formulation and evaluation of hard capsule containing Houttuynia cordata extract - Tran , Thị Mỹ Tâm; Nguyen , Hồng Sơn; Vu, Lê Hà; Huynh, Lời (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Houttuynia cordata, a medicinal herb with several health benefits, which is widely used for the treatment of hemorrhoid. The aim of this study is to formulate the hard capsule containing Houttuynia cordata extract. Herba Houttuynia cordata was extracted by using 96 % ethanol. The capsule was formulated by using various excipients including gồm aerosil, avicel, natri croscarmellose, and talc. The granules were prepared by wet granulation process. The formula is selected based on various criteria such as moisture, uniformity of weight, quanlitative research, quantitative research, and disintegration of the hard capsules according to the Vietnamese Pharmacopoeia V. The amount of flavonoid was determined by UV-VIS method. Total flavonoid and moisture content in crude 96 % ethanol extract was 2.1 % and 13.1 %, respectively. The capsule contains 35 % of ethanol extract, 15% of aerosil, 47 % of avicel, 2 % of natri croscarmellose, and 1 % of talc. Moisture, uniformity of weight, quanlitative research, quantitative research, and disintegration of the capsule comply with the requirements for monographs in the Vietnamese Pharmacopoeia V.